Analysis of Overcoming Cyberbullying through Digital Literacy Education - Amrullah, Muhlasin; Wardana, Mahardika D. K.; Hikmah, Khizanatul; Cahyanti, Novita Nur; Fatikha, Salsabila (Proceeding International Conference on Lesson Study, 2023)
Understanding the use of technology is important, especially for the majority of children who are teenagers. Cyberbullying often becomes a scourge in itself when there is a lack of digital literacy education. This research aims to see the impact of strengthening and strengthening children's knowledge about the dangers of Cyberbullying as well as familiarizing the children with the importance of digital literacy in the Sidoarjo Orphanage. Descriptive qualitative research method with counseling stages regarding Cyberbullying, and digital literacy education which consists of collecting data through tests which will be carried out using perception questionnaires, and a pretest posttest at the end of the activity. In the research, the results showed that understanding cyberbullying and digital literacy education can improve the perception of children in orphanages regarding several events that will often be encountered in the environment. This is proven by the increase in children's knowledge regarding the impact of cyberbullying and digital literacy, which increased by 80 percent from a total of 14 children in orphanages through a perception test questionnaire.